Taxonomic review and phylogenetic analysis of Microcharops Roman, 1910 (Hymenoptera: Ichneumonidae: Campopleginae) - Santos, Alvaro Doria dos (2024)
Ichneumonidae is the largest family of the order Hymenoptera (which includes ants, bees, and wasp). Popularly known as Darwin wasps, the Ichneumonidae comprises more than twenty-five thousand species and 1.600 genera. Among them, Microcharops, a New World genus of Darwin wasps comprises 23 valid species. Microcharops females are known for their parasitic behavior targeting Lepidopteran hosts. Many species of Microcharops spin their cocoons within the larval skin of the host, forming a \"mummy\" if the host cuticle is sufficiently thick. A comprehensive revision of this genus was undertaken in 1987 where 15 species were described, and five species groups were proposed. After this pioneer revision, few studies explored Microcharops at species level. The limited research in this area could be attributed to the ongoing uncertainty in defining species boundaries. Consequently, accurately identity of collected specimens still relied on direct side-by-side comparisons with the type specimens. The current circumstances motivate us to work on a comprehensive taxonomic revision of Microcharops and to investigate its interspecific relationships through a phylogenetic analysis. Our taxonomic revision identified 31 species within the Microcharops genus. Studying intraspecifc variation we synonymized Microcharops nigricoxa, M. anticarsiae, M. bimaculate, M. peronotus. Also, twelve new species were described. Our phylogenetic analysis did not recover the species grouping established in the first taxonomical revision as a natural group. Based on our analysis, we propose the hypothesis that the Microcharops clade may have evolved from a more specialized parasitoid of Nymphalid hosts to a more derived generalist strategy. We also provided illustrations of all type specimens, distribution maps and a key for all Microcharops species.